Publication of the Memories of Zdena Masinova jr. - Danicek, Patrik (Historica Olomucensia, 2019)
In this article, the author maps the life of a member of the Czechoslovak legions, the army of Czechoslovakia and anti-Nazi resistance, general in memoriam Josef Masin. His life in not presented on a research of archive sources or literature, but on memories of his daughter, Zdena Masinova jr.The picture of the hero of the anti-Nazi resistance is presented through eyes of his youngest descendant, thanks to the memories of Zdena Masinova jr. the reader gets acquainted with up to now unknown details of the life of general Josef Masin and other members of the Masin family.Zdena Masinova jr. also depicts the afterwar period and the efforts of her mother to find her husband and to get more adequate recognition of his resistance merits and also talks about finding the kites that general Masin left in his cell in Pankrac prison that created a legacy for his children. At the end, Zdena Masinova jr. describes her life in communism and her fight to get their family homestead back.
Keywords: Josef Masin; Czechoslovak army; Three Kings; anti-Nazi resistance; Zdena Masinova older; Masin brothers; Zdena Masinova younger